Larvicidal Efficacy of Abamectin–Pyriproxyfen Mixtures Against Musca domestica in a Poultry Farm: A Field Evaluation - Alamil Jr. , Cesar Daseco; Purnamasari, Listya; Lauron, Meriam C.; dela Cruz, Joseph F. (Andalasian International Journal of Entomology, 2026)
The house fly, Musca domestica, is a notorious veterinary pest that has developed resistance to insecticides. One approach to address this concern is by mixing insecticides to overcome resistance and accelerate pest management. This study was conducted to evaluate the larvicidal efficacy of the abamectin and pyriproxyfen binary mixture against M. domestica larvae, based on its ability to reduce larval populations and inhibit pupal formation. The study was conducted in the UPLB VTH Experimental Poultry House. Forty-five boxes, each containing 500 larvae, were distributed across five treatment groups, with nine replicates per treatment. The treatments consisted of distilled water (T1), low-concentration pyriproxyfen (T2), high-concentration pyriproxyfen (T3), low-concentration abamectin-pyriproxyfen binary mixture (T4), and high-concentration abamectin-pyriproxyfen binary mixture (T5). The treatments were applied to each box on days 0 and 7, and the number of live larvae and pupae was recorded on days 7 and 14. On day 7, T5 achieved the highest larval reduction of 88.49%, which was significantly higher than the other treatments. By day 14, T3, T4, and T5 exhibited comparable larval reduction with no significant differences among them. In terms of day 7 pupal inhibition, T5 had the highest inhibition at 95.75%, followed closely by T3 and T4, with no significant difference among the three. By day 14, T5 again had the highest effect at 95.26%, with T3 and T4 also showing similarly strong results. The results of this study highlight the potential of the abamectin-pyriproxyfen binary mixture as a tool in managing house fly populations. However, the lack of significant differences between the binary mixture and the high-concentration pyriproxyfen suggested that the enhanced efficacy was not substantial.